Modeling Immune Response to Leishmania Species Indicates Adenosine As an Important Inhibitor of Th-Cell Activation - Ribeiro, Henrique A. L.; Maioli, Tatiani U.; de Freitas, Leandro M.; Tieri, Paolo; Castiglione, Filippo (Frontiers in Cellular and Infection Microbiology, 2017)
Infection by Leishmania protozoan parasites can, depending on the parasite species, cause a variety of disease outcomes in humans and other mammals, from single self-healing cutaneous lesions to a visceral dissemination of the parasite. The correlation between chronic lesions and ecto-nucleotidase activity on the surface of the parasite is addressed here using damage caused in epithelial cells by nitric oxide. In order to explore the role of purinergic metabolism in lesion formation and the outcome of the infection, we implemented a cellular automata/lattice gas model involving major immune characters (Th1 and Th2 cells, IFN-γ, IL-4, IL-12, adenosine (Ado), NO) and parasite players for the dynamic analysis of the disease progress. Important characteristics of the model were analyzed using partial ranking correlation coefficient (PRCC) to indicate the components that most influence the disease progression. The model showed that T-cell activation, Th-cells survival and Leishmania survival probabilities are common parameters among Leishmania infection simulated here. Low Ado inhibition rate over Th-cells is shared by L. major and L. braziliensis, while in L. amazonensis infection the Ado inhibition rate over Th-cells reaches 30%. IL-4 inhibition rate over Th-cell priming to Th1 independent of IL-12 are exclusive of L. major. The lesion size and progression showed agreement with published biological data and the model was able to simulate cutaneous leishmaniasis. The sensibility analysis suggested that Ado inhibition rate over Th-cells followed by Leishmania survival probability were the most important characteristics of the simulation, with PRCC of 0.89 and 0.77 respectively. The simulations also showed a non-linear relationship between Ado inhibition rate over Th-cells and lesion size measured as number of dead epithelial cells. In conclusion, this model is a useful tool for understanding the immune response in leishmaniasis.